Social Psychological Characteristics Of Stress Prevention In The Professional Activity Of Teachers (Zien Journal of Social Sciences and Humanities, 2024)
The article describes professional stress and its impact on employee performance. It also analyzes the socio-psychological factors that influence stress prevention and practical strategies that can be implemented in the professional environment to mitigate stress.